INDIVIDUAL PSYCHOLOGICAL PROPERTIES OF THE WORLD - Izatovna, Toyirova Laylo; Sattorivich, 2Nazarov Azamat (International Journal of Psychosocial Rehabilitation, 2020)
This article presents a theoretical and practical analysis of research findings revealing the causes that characterize the individual psychosocial features and personality traits of identiflying twins.